Sexual Gratification As A Serious Threat In Modern Criminal Reasoning On Aspects Of Judges' Considerations In Court Judgment - Muhamad Iqbal; Susanto; Bhanu Prakash Nunna (Jurnal Jurisprudence, 2023)
ABSTRACT Objective: This research aims to examine and analyze the problem of sexual gratification as a serious threat in modern criminal reasoning. Methodology: In this research, the authors used a normative juridical method. This method was employed to examine many types of legal materials by referring to diverse norms found in legislation and encompassing several related legal principles, history, doctrine, and jurisprudence. Thus, this method applied a statutory approach. Finding: Over time, since all kinds of gifts within the scope of gratification have developed, the segmentation has become wider. This suggests that valuable facilities and objects are not only money and luxury facilities but also anything that can facilitate all kinds of individual biological needs, such as sexual. Sexual gratification, which originated from prohibited activities against the law with different scopes, such as prostitution, has now been targeted as a gift in the form of sexual facilities as an effort or reward for prohibited services provided by legal subjects in the Corruption Eradication Law. In relation to several things, in this aspect, the regulation in practice still has difficulty enforcing the law on the issue of gratification, considering the difficulty of providing evidence in the regulation. As such, an alternative step in this aspect is to find a legal breakthrough, one of which is using the judge's authority at the examination stage. As happened in Court Judgment Number 87/PID.SUS/TPK/2013/PN.BDG, the fact was discovered that one of the witnesses in court stated that the Defendant asked for sexual services every Thursday or Friday night, but this was not considered in legal considerations. In fact, her statement should have been used as evidence against the Defendant. For this reason, modern criminal reasoning in the form of adjustments to the development of sexual gratification crimes is an effort to protect the nation. In arrangements relating to gratuities, there is a context relating to "other facilities"; here, it is considered that the context of sexuality can be included in the realm of gratification. In the context of "means," it is often categorized as a form of tool to achieve a desired goal. Application of this study: It is expected that this research can support literacy in society in all segments in responding to developments in the context of gratification to carry out prevention and legal developments regarding society's need for protection from threats, especially regarding morality in society. Sexual gratification is considered to be a serious threat to the moral values that live in society, considering that sexual gratification is not only a loss to the state but also a threat to the norms of decency that live in society. Novelty/Originality: In contrast to previous research, this research focuses on aspects of sexual gratification and the impact of morality in the interests of modern criminal law in criminal acts of corruption, which have not been specifically researched until now. Keywords: Criminal Act; Corruption; Sexual Gratification ABSTRAK Tujuan: Penelitian ini bertujuan untuk mengkaji dan menganalisis permasalahan kepuasan seksual sebagai ancaman serius dalam penalaran pidana modern. Metodologi: Dalam penelitian ini penulis menggunakan metode yuridis normatif. Metode ini digunakan untuk mengkaji berbagai jenis bahan hukum dengan mengacu pada beragam norma yang terdapat dalam peraturan perundang-undangan dan mencakup beberapa asas hukum, sejarah, doktrin, dan yurisprudensi yang terkait. Dengan demikian, metode ini menerapkan pendekatan perundang-undangan. Temuan: Seiring berjalannya waktu, sejak berkembangnya segala jenis pemberian dalam lingkup gratifikasi, maka segmentasinya menjadi lebih luas. Hal ini menunjukkan bahwa fasilitas dan benda yang berharga bukan hanya sekedar uang dan fasilitas kemewahan tetapi juga segala sesuatu yang dapat memfasilitasi segala macam kebutuhan biologis individu, misalnya seksual. Gratifikasi seksual yang bermula dari kegiatan-kegiatan yang dilarang melawan hukum dengan cakupan yang berbeda-beda, misalnya prostitusi, kini di sasaran sebagai pemberian berupa fasilitas seksual sebagai upaya atau imbalan atas jasa-jasa terlarang yang diberikan oleh subjek hukum dalam UU Pemberantasan Tipikor. Terkait dengan beberapa hal, pada aspek ini, peraturan tersebut dalam praktiknya masih mengalami kesulitan dalam menegakkan hukum terhadap masalah gratifikasi, mengingat sulitnya pembuktian dalam peraturan tersebut. Oleh karena itu, langkah alternatif dalam aspek ini adalah dengan mencari terobosan hukum, salah satunya dengan menggunakan kewenangan hakim pada tahap pemeriksaan. Sebagaimana terjadi dalam Putusan Pengadilan Nomor 87/PID.SUS/TPK/2013/PN.BDG, ditemukan fakta bahwa salah satu saksi di persidangan menyatakan bahwa Terdakwa meminta layanan seksual setiap hari Kamis atau Jumat malam, namun hal tersebut tidak dipertimbangkan. dalam pertimbangan hukum. Padahal, keterangannya seharusnya dijadikan alat bukti yang memberatkan Terdakwa. Untuk itu penalaran pidana modern berupa penyesuaian terhadap perkembangan kejahatan gratifikasi seksual merupakan upaya perlindungan bangsa. Dalam pengaturan terkait gratifikasi, terdapat konteks yang berkaitan dengan “fasilitas lain”; di sini, konteks seksualitas dianggap bisa masuk dalam ranah gratifikasi. Dalam konteks “sarana”, sering kali dikategorikan sebagai suatu bentuk alat untuk mencapai tujuan yang diinginkan. Kegunaan: Diharapkan penelitian ini dapat mendukung literasi masyarakat pada semua segmen dalam menyikapi perkembangan dalam rangka gratifikasi untuk melakukan pencegahan dan pengembangan hukum mengenai kebutuhan masyarakat akan perlindungan dari ancaman khususnya mengenai moralitas dalam masyarakat. Gratifikasi seksual dinilai dapat menjadi ancaman serius terhadap nilai-nilai moral yang hidup dalam masyarakat, mengingat kepuasan seksual tidak hanya merugikan negara tetapi juga merupakan ancaman terhadap norma kesusilaan yang hidup dalam masyarakat. Kebaruan/Keaslian: Berbeda dengan penelitian-penelitian sebelumnya, penelitian ini berfokus pada aspek kepuasan seksual dan dampak moralitas untuk kepentingan hukum pidana modern dalam tindak pidana korupsi yang hingga saat ini belum diteliti secara khusus. Kata Kunci: Tindak Pidana; Korupsi; Kepuasan Seksual